3D/3D Hetero‐Interpenetrating Diamondoid Framework and Homo‐Interpenetrating pcu Network by a One‐Pot Reaction. Issue 15 (24th April 2014) - Guo, Xiang‐Guang; Yang, Wen‐Bin; Wu, Xiao‐Yuan; Lin, Lang; Lu, Can‐Zhong
Abstract: Two new metal–organic frameworks (MOFs) with novel architectures, namely, [Co2 (NDC)2 (H2 MDP)2 ][(Co(NDC)(H2 MDP)] (1 ) and [Co(NDC)(H2 MDP)0.5 ] (2 ) were synthesized through a one‐pot reaction. The metal to ligand ratio was found to influence the formation of the two compounds, and their pure phases were successfully obtained only by adjusting the molar ratios of Co/H2 NDC/H2 MDP to be 1:1:1 and 2:2:1, respectively [H2 NDC = 1, 4‐naphthalenedicarboxylic acid, H2 MDP = methylenebis(3, 5‐dimethylpyrazole)]. X‐ray crystallographic analyses showed that1 crystallizes as a racemic twin and features an interesting threefold 3D/3D hetero‐interpenetrating diamondoid framework with left‐handed and right‐handed helical chains, whereas2 displays a 3D twofold homo‐interpenetrating pcu network constructed from paddle‐wheel secondary building units and H2 MDP pillars in a trans conformation. The one‐pot synthesis of two or more MOFs with hetero‐interpenetration and homo‐interpenetration has been rarely reported. Abstract : Two new compounds, one with a 3D/3D hetero‐interpenetrating diamondoid framework and the other with a homo‐interpenetrating pcu network, are synthesized through a one‐pot reaction. Their pure phases are obtained by adjusting the metal/ligands ratio. The magnetic properties of the homo‐interpenetrating network are investigated.